A Virtue Ethic for the Earth - de Groot, Wouter T.; Knippenberg, Luuk (Journal of Ecohumanism, 2023)
Discussions and practices for biodiversity and the environment are associated predominantly with duty ethics, which spell out the do’s and don’ts of good behavior. Virtue ethics offer an alternative that is much more inspirational, provided we do not reduce it to a mere enumeration of environmental virtues. Moreover, a virtue ethic is truly humanistic, in that it builds on inborn human capacities rather than on external sources of morality. Grounded in the classic Greek account of virtue ethics and in interaction with medieval and modern visions, this paper articulates a virtue ethic for the Earth. Accessible to a broad audience, we address the foundational concepts of nature-inclusive telos, eudaimonia, virtues and friendship, and connect these with social-scientific research findings. This elucidates how the virtues, sometimes supported by moral exemplars, work in lives that include nature in their flourishing. A virtue ethic for the Earth, we think, can be helpful for policy making but most of all act as a platform for people to become more inspired, courageous and effective friends of nature and the planet as a whole.